THU0243 HSA_CIRC_0123190 FUNCTIONS AS A COMPETITIVE ENDOGENOUS RNA TO REGULATE APLNR EXPRESSION BY SPONGING HSA-MIR-483-3P IN LUPUS NEPHRITIS. (2nd June 2020) - Zhang, C.; Gao, C.; Di, X.; Cui, S.; Liang, W.; Sun, W.; Yao, M.; Wang, Q.; Zheng, Z.
Abstract : Background: Lupus nephritis (LN) is one of the most severe complications of systemic lupus erythematosus (SLE). Circular RNAs(circRNAs) can act as competitive endogenous RNAs (ceRNAs) to regulate gene transcription, which is involved in mechanism of many diseases, such as, autoimmunity diseases. However, the role of circRNA in lupus nephritis has been rarely reported. Objectives: In this study, we aim to investigate the clinical value of circRNAs and explore the mechanism of circRNA involvement in the pathogenesis of LN. Methods: Renal tissues from three untreated LN patients and three normal controls (NCs) were used to identify differently expressed circRNAs by RNA sequencing (RNA-seq). Validated assays were used by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Correlation analysis and receiver operating characteristic (ROC) curve were used to reveal the clinical value of selected circRNA, miRNA and mRNA. The interactions between circRNA and miRNA, or miRNA and mRNA were further determined by luciferase reporter assay. The degrees of renal fibrosis between the two groups were compared by Masson-trichome staining and immunohistochemistry staining. Results: 159 circRNAs were significantly dysregulated in LN patients compared with NC group. The expression of hsa_circ_0123190 was significantly decreased in renal tissues of patients with LN ( p =0.014), as same as the sequencing results. The area under the ROC curve of hsa_circ_0123190 in renal tissues was 0.820. Bio-informatic analysis and luciferase reporter assay illustrated that hsa_circ_0123190 can act as a sponge for hsa-miR-483-3p which was also validated to interact with APLNR mRNA. APLNR mRNA expression was positively related with chronicity index (CI) of LN (R 2 =0.452, p =0.033). Finally, the factors of renal fibrosis, especially TGF-β ( p =0.018), were more pronounced in the LN group. Conclusion: Hsa_circ_0123190 could function as a ceRNA to regulate APLNR expression involved in renal fibrosis by sponging hsa-miR-483-3p in LN References: [1]Aljaberi N, Bennett M, Brunner HI, Devarajan P. Proteomic profiling of urine: implications for lupus nephritis. Expert review of proteomics. 2019;16(4):303-13. [2]Zheng ZH, Zhang LJ, Liu WX, Lei YS, Xing GL, Zhang JJ, et al. Predictors of survival in Chinese patients with lupus nephritis. Lupus. 2012;21(10):1049-56. [3]Chen LL. The biogenesis and emerging roles of circular RNAs. Nature reviews Molecular cell biology. 2016;17(4):205-11. [4]Mahmoudi E, Cairns MJ. Circular RNAs are temporospatially regulated throughout development and ageing in the rat. Scientific reports. 2019;9(1):2564. [5]Liang D, Wilusz JE. Short intronic repeat sequences facilitate circular RNA production. Genes & development. 2014;28(20):2233-47. [6]Tan WL, Lim BT, Anene-Nzelu CG, Ackers-Johnson M, Dashi A, See K, et al. A landscape of circular RNA expression in the human heart. Cardiovascular research. 2017;113(3):298-309. [7]Zhao Z, Li X, Jian D, Hao P, Rao L, Li M. Hsa_circ_0054633 in peripheral blood can be used as a diagnostic biomarker of pre-diabetes and type 2 diabetes mellitus. Acta diabetologica. 2017;54(3):237-45. [8]Ouyang Q, Huang Q, Jiang Z, Zhao J, Shi GP, Yang M. Using plasma circRNA_002453 as a novel biomarker in the diagnosis of lupus nephritis. Molecular immunology. 2018;101(undefined):531-8. [9]Luan J, Jiao C, Kong W, Fu J, Qu W, Chen Y, et al. CircHLA-C Plays an Important Role in Lupus Nephritis by Sponging miR-150. Molecular therapy Nucleic acids. 2018;10(undefined):245-53. [10]Kuschnerus K, Straessler ET, Müller MF, Lüscher TF, Landmesser U, Kränkel N. Increased Expression of miR-483-3p Impairs the Vascular Response to Injury in Type 2 Diabetes. Diabetes. 2019;68(2):349-60. [11]Huang Z, Wu L and Chen L. Apelin/APJ system: A novel potential therapy target for kidney disease. Journal of cellular physiology. 2018;233(5): 3892-900. Disclosure of Interests: None declared